Identifying profiles of actual and perceived motor competence among adolescents: associations with motivation, physical activity, and sports participation. Issue 21 (1st November 2016) - De Meester, An; Maes, Jolien; Stodden, David; Cardon, Greet; Goodway, Jacqueline; Lenoir, Matthieu; Haerens, Leen
ABSTRACT: The present study identified adolescents' motor competence (MC)-based profiles (e.g., high actual and low perceived MC), and accordingly investigated differences in motivation for physical education (PE), physical activity (PA) levels, and sports participation between profiles by using regression analyses. Actual MC was measured with the Körperkoordinationstest für Kinder. Adolescents ( n = 215; 66.0% boys; mean age = 13.64 ± .58 years) completed validated questionnaires to assess perceived MC, motivation for PE, PA-levels, and sports participation. Actual and perceived MC were only moderately correlated and cluster analyses identified four groups. Two groups of overestimators (low – overestimation, average – overestimation) were identified (51%), who particularly displayed better motivation for PE when compared to their peers who accurately estimated themselves (low – accurate, average – accurate). Moreover, adolescents with low actual MC, but high perceived MC were significantly more active than adolescents with low actual MC who accurately estimated themselves. Results pointed in the same direction for organised sports participation. Underestimators were not found in the current sample, which is positive as underestimation might negatively influence adolescents' motivation to achieve and persist in PA and sports. In conclusion, results emphasise that developing perceived MC, especially among adolescents with low levels of actual MC, seems crucial to stimulate motivation for PE, and engagement in PA and sports.